A distância entre dois mundos: o encontro do Ocidente com o Oriente na perspectiva indiana de Thrity Umrigar - Soares, Aline de Mello (2012)
The present dissertation concerns the study of two novels by the Indian writer Thrity Umrigar, If today be sweet (2007) and The weight of heaven (2009), which tell stories of migrations India-United States, United States-India, respectively. The study intends to analyse the representation created by Umrigar of the cultural shock caused by the encounter of two worlds the Orient and the West different in habits, values, behavior, points-of-view. Elements of post colonial Indian literature as well as theoretical referents related to culture and what surrounds it taken from Edward Said, Homi Bhabha, Terry Eagleton and Zygmunt Bauman will be used to substantiate this work.